ACHYRANTHUS ASPERA - MEDICINAL PLANT: A REVIEW - RAJI R (International Journal of Pharma and Bio Sciences, 2013)
Achyranthes aspera (Amaranthaceae) is an important medicinal herb found as a weed throughout India. Though almost all of its parts are used in traditional systems of medicines, seeds, roots and shoots are the most important parts which are used medicinally. The present article gives an account of updated information on its phytochemical and pharmacological properties.